Effects of abrasion on mechanical properties of Kevlar KM2-600 and S glass tows. Issue 6 (March 2019) - Abu Obaid, A; Gillespie, JW
In this effort, the effects of abrasion on the mechanical properties of Kevlar KM2-600 and two types of S glass tows (AGY S2 and Owens Corning Shield Strand S) are studied. Data was generated from cyclic abrasion tests conducted at a tension level of 8% of failure load at10 mm/s (24 in/min) using a specially developed abrasion test machine. Fit curves for axial modulus and tenacity loss were established as a function of abrasion time/contact length for each tow type. Fiber surface damage and fiber breakage within the tows were identified as the major source of tow property degradation. Based on scanning electron microscopy measurements, glass fibers exhibited surface damage (micro-cracks and sizing/coating removal) that were more extensive in AGY S2 glass fibers. Kevlar KM2 fibers after tow abrasion tests exhibited fibrillation and peeling of broken fibrils from the fiber surface. In all three fibers, surface damage increased at longer abrasion times/friction contact length. Overall, the results indicated that the abrasion resistance is the highest for Kevlar KM2, followed by OCV Shield Strand and AGY S2 glass tows. The sizing material on OCV Shield Strand fibers contributed to the improved abrasion resistance compared to AGY S2.